REVIEWS. Issue 1 (10th August 2012) - Royal, Derek Parker; Abrams, Rachel; Lightman, Sarah; Murray, Chris; Cortsen, Rikke Platz; Hague, Ian
African-American Classics, Tom Pomplun and Lance Tooks (eds) (2011) Mount Horeb, WI: Eureka Productions, 144 pp., $17.95. Paperback ISBN 9780982563045The Silence of Our Friends, Mark Long, Jim Demonakos and Nate Powell (2012) New York: First Second, 201 pp., $16.99. Paperback ISBN 9781596436183The Graphic Details Symposium, at the Center for Jewish History, New York City, 26 February 2012Graphic Women: Life Narrative & Contemporary Comics, Hillary L. Chute (2010) New York Chichester, West Sussex: Columbia University Press, 297 pp., £18.50. Paperback ISBN: 9780231150620 1001 Comics You Must Read Before You Die, Paul Gravett (ed.) (2010) Cassell Illustrated/Quintessence Editions Ltd, 960pp., £20. ISBN: 97884403698Grant Morrison - Combining the Worlds of Contemporary Comics, Marc Singer (2012) Jackson: University Press of Mississippi, 323 pp., $25. PaperbackISBN: 9781617031366First International Conference on Comics and Graphic Novels: Sites of Visual and Textual Innovation, Instituto Franklin-UAH, Alcalá de Henares, Spain, 9–12 November 2011